Crop Considerations for Citrus Lands - Stephen H. Futch; Brent A. Sellers (EDIS)
HS-1062, a 5-page illustrated fact sheet by Stephen H. Futch and Brent A. Sellers, discusses herbicide residues on citrus land where the trees have been removed due to citrus canker, and issues to address before the acreage can be converted to other agricultural uses. The authors describe bioassay procedures and tests for specific herbicide groups. Includes a table of relevant data for herbicide products frequently used in Florida citrus production. Published by the UF Department of Horticultural Sciences, March, 2006.